2006
DOI: 10.1111/j.1439-0507.2006.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticandidal activity of Pseudomonas aeruginosa strains isolated from clinical specimens

Abstract: Pseudomonads represent the major group of non-differentiating microorganisms that produce antibiotics. The antibiotic substances produced by this group of organisms are pyocyanin, pyrolnitrin and pseudomonic acid. This study was designed to investigate the in vivo and in vitro anticandidal activity of Pseudomonas aeruginosa strains against Candida species. Forty-four P. aeruginosa strains isolated from various specimens of intensive care patients were included in the study. All P. aeruginosa strains have pyocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
(59 reference statements)
1
27
0
Order By: Relevance
“…The first is based on the observation that virulent P. aeruginosa strains; including PA14 kill yeast [54],[55],[56]; and the second is based on that P. aeruginosa can infect and kill Drosophila melanogaster [57],[58],[59], and that mvfR mutant cells exhibit attenuated virulence in flies [57]. As illustrated in Figure 1C–D, a zone of yeast growth inhibition was observed around PA14, but not around the mvfR − , or pqsE − mutants following plating of C. neoformans KN99α 5 mm from the bacterial colony on a YPD plate (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…The first is based on the observation that virulent P. aeruginosa strains; including PA14 kill yeast [54],[55],[56]; and the second is based on that P. aeruginosa can infect and kill Drosophila melanogaster [57],[58],[59], and that mvfR mutant cells exhibit attenuated virulence in flies [57]. As illustrated in Figure 1C–D, a zone of yeast growth inhibition was observed around PA14, but not around the mvfR − , or pqsE − mutants following plating of C. neoformans KN99α 5 mm from the bacterial colony on a YPD plate (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used the term ‘mixed Candida /bacterial BSI’ to describe the isolation of bacterial species within 48 h of the time of candidaemia to avoid confusion with previous studies. We chose this definition because concomitant bacteraemia may obscure the detection of fungaemia using standard blood culture techniques by suppression of fungal growth [9,10,26]. The inclusion of only synchronous candidaemia and bacteraemia could cause the underestimation of the incidence of mixed Candida /bacterial BSIs.…”
Section: Discussionmentioning
confidence: 99%
“…Both morphological forms are important for virulence, and the ability to undergo morphological transformation is therefore an important virulence trait (Gow, 1997;Calderone and Fonzi, 2001;Gow et al, 2002;Liu, 2002;Whiteway and Oberholzer, 2004). Several studies have suggested that P. aeruginosa may inhibit C. albicans growth within the host (Bauernfeind et al, 1987;Kerr, 1994;Burns et al, 1999;Gupta et al, 2005;Kaleli et al, 2007). Hogan and Kolter (2002) demonstrated that P. aeruginosa is cytotoxic to the filamentous form of C. albicans but is unable to attach to or kill C. albicans yeast cells.…”
Section: Introductionmentioning
confidence: 99%